2002
DOI: 10.1046/j.1365-2206.2002.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting children's rights through the use of relationship

Abstract: This paper reports on a research study exploring the views of 27 children and young people on their involvement in a child protection investigation. Their perspectives on the personal and professional qualities of the professionals involved and on the choice, influence and representation they experienced and prefer are discussed. One of the most striking findings is that most of the children and young people had experienced a positive relationship with a social worker. Overall, many reported improvements at ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 11 publications
9
114
1
6
Order By: Relevance
“…Social workers should share information with children and young people and provide support for them to understand assessments and reports (Bell, 2002;Cleaver et al, 2004). This should be done in an accessible way to enable children to understand what is going on in their lives; yet the 2 reports shared in this study were by a teacher and a parent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social workers should share information with children and young people and provide support for them to understand assessments and reports (Bell, 2002;Cleaver et al, 2004). This should be done in an accessible way to enable children to understand what is going on in their lives; yet the 2 reports shared in this study were by a teacher and a parent.…”
Section: Discussionmentioning
confidence: 99%
“…However, maltreated children who are not involved may be left with feelings of powerlessness (Bell, 2002). Direct research with children carried out by Milner and Carolin (1999) showed that children and young people felt that they were not important and social workers did not listen to them.…”
Section: 'Participation By Children Matters Not Only Because It Is Amentioning
confidence: 99%
“…Participation can be protective for vulnerable children, leading to increased confidence, self-efficacy and self-worth (Limber & Kaufman 2002;Schofield 2005). Not involving maltreated children may compound or reactivate feelings of powerlessness (Bell 2002). Maltreatment can be seen as a violation of a child's human rights.…”
Section: Introductionmentioning
confidence: 99%
“…So preparing a child for and facilitating their appropriate involvement involves explaining the process and exploring the choices and boundaries of decision-making as well as enabling them to decide what, for them, is the best means of participating, be it being present in a meeting, in writing or through the use of an advocate (Bell, 2002). Some children will need help in devising symbolic means of communicating their wishes.…”
Section: Social Work Trainingmentioning
confidence: 99%